2020
DOI: 10.1111/jrh.12458
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the Time of COVID‐19: A Perfect Storm

Abstract: Key words coronavirus pandemic, COVID-19, I 3 model, perfect storm theory, suicide.In this commentary, we consider a convergence of suicide risk factors amid an international crisis and introduce a new approach in understanding and preventing suicidal behaviors. Our approach is a novel theoretical framework that can guide future research to include this added dimension.Suicide is a leading cause of death in the United States and Kentucky. In the United States, suicide rates have steadily risen over the past 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 14 publications
0
45
0
7
Order By: Relevance
“…Despite aggressive public health interventions in place to combat the novel coronavirus (COVID‐19) around the globe, mental health prevention and intervention practices have lagged behind. Not surprisingly, a growing number of European and Chinese COVID‐19 studies report significant mental health consequences for isolated, fragmented, and distraught populations (Brown & Schuman, 2020; Cowan, 2020; de Girolamo et al., 2020; Qui et al., 2020; Sonderskov, Dinesen, Santini, & Ostergaard, 2020; Stankovaska, Memedi, & Dimitrovski, 2020; Wang, Di, Ye, & Wei, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite aggressive public health interventions in place to combat the novel coronavirus (COVID‐19) around the globe, mental health prevention and intervention practices have lagged behind. Not surprisingly, a growing number of European and Chinese COVID‐19 studies report significant mental health consequences for isolated, fragmented, and distraught populations (Brown & Schuman, 2020; Cowan, 2020; de Girolamo et al., 2020; Qui et al., 2020; Sonderskov, Dinesen, Santini, & Ostergaard, 2020; Stankovaska, Memedi, & Dimitrovski, 2020; Wang, Di, Ye, & Wei, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As the COVID‐19 pandemic unfolded, researchers began noting a potential for an unusually high level of susceptibility to extreme mental health consequences, including both suicide ideation and attempts (Brown & Schuman, 2020; Reger, Stanley, & Joiner 2020). The hypersensitivity to the novel coronavirus (COVID‐19) has added a layer of risk to personal safety as the pandemic continues to alter people’s daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing novel coronavirus pandemic has wrought in its wake economic and social devastation. As people struggle to cope with the immediate and long-term consequences of the pandemic, many of the resources traditionally used to cope with stress, such as social support, are no longer available or accessible; the result is a “perfect storm” for suicide ( Brown and Schuman, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study reporting on the long-term effects of SARS quarantine among healthcare workers found a long-term risk for alcohol abuse, self-medication and long-lasting "avoidance" behavior -where some hospital workers avoid being in close contact with patients by simply not showing up for work. Scientists predict that, if the pandemic continues, psychological and social effects of Covid-19 will worsen and create the "perfect storm" of conditions for suicide, especially in the most vulnerable categories, like the elderly, poor and people suffering from previous mental problems [66].…”
Section: Psychological Impactmentioning
confidence: 99%